Theoretical study of electronic and structural properties of N-(2-OXO-2H-CHROMEN-3-CARBONYL) cytisine - Turdybekov, D.M.; Ibrayev, N.Kh.; Kopbalina, K.B.; Kishkentayeva, А.; Pankin, D.V.; Smirnov, M.B. (Buketov Karaganda National Research University, 2025)
New compounds based on cytisine and coumarin are of interest to the pharmaceutical industry due to their promising biological activity. This activity, in turn, is closely related to the structure of the compound, which is manifested in its specific electronic properties. This paper presents the results of a theoretical study of the electronic and structural properties of recently synthesized N-(2-oxo-2H-chromen-3-carbonyl)cytisine. The molecular structure of the ground and first excited states is established. Their structural features are considered, taking into account their conformational diversity. The probabilities of vertical electronic transitions, which determine the intensities of bands in the emission spectrum, are calculated. The obtained theoretical results are compared with the measured luminescence spectrum of ethanol solution.
Keywords: cytisine; coumarin; complex; density functional theory; Ultraviolet–visible spectroscopy; luminescence spectroscopy